Agache's Measuring the Skin : Non-invasive Investigations, Physiology, Normal Constants - Humbert, Philippe; Fanian, Ferial; Maibach, Howard I.; Agache, Pierre (Springer International Publishing : Imprint: Springer, 2017)
Since the first edition of this book was published in 2004, to much acclaim, the pace of innovation in the field of skin metrology has increased and various new technologies have become available. This new, revised edition reflects these advances by presenting the current theory and practice of noninvasive investigation and measurement of the skin and its appendices in health and disease. The first, extensive part of this authoritative work is devoted to the physiology and metrology of the various structural components of the skin. Skin functions and their measurement are then discussed in detail, with sections on mechanical protection, photoprotection, barrier function, immune function, thermoregulation, and sensory function. In addition, careful consideration is given to skin disease rating and skin maps, and a unique list of physical and biological constants and units is provided. Not only is this new edition the first comprehensive, practical handbook in this domain - it will also serve as a manual of skin physiology and collates anatomical, functional, and physical quantitative data that would otherwise be arduous to retrieve because of their dispersal throughout the literature. It will prove a valuable resource for dermatologists, cosmetologists, bioengineers, physiologists, pharmacists, and all others who deal with the skin in their work.
Keywords: Medicine.; Pharmacology.; Dermatology.; elektronické knihy; electronic books